2012
DOI: 10.1007/s00383-012-3169-4
|View full text |Cite
|
Sign up to set email alerts
|

Practice of dilatation after surgical correction in anorectal malformations

Abstract: Considering the high number of painful treatments, predictors for painful dilatations should be further clarified through standardized documentation and prospective evaluation in order to improve follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 7 publications
1
27
0
Order By: Relevance
“…The dilatations are mostly performed for a period of 6 to 8 months. 7 More recently, weekly calibration by a surgeon has been shown to achieve similar functional outcomes compared with daily parental dilatations and avoiding the psychological stress on the parents. 5 The practice in center A is to dilate neonates up to Hegar size 14, close the stoma and, often to continue using suppositories thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dilatations are mostly performed for a period of 6 to 8 months. 7 More recently, weekly calibration by a surgeon has been shown to achieve similar functional outcomes compared with daily parental dilatations and avoiding the psychological stress on the parents. 5 The practice in center A is to dilate neonates up to Hegar size 14, close the stoma and, often to continue using suppositories thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…4 Jenetzky et al also reported comparable stricture rates following definitive surgery for ARM regardless of use of RPD. 7 Our study has assessed outcomes following RPD or otherwise in two major United Kingdom pediatric surgical centers. We observed no significant differences in need for further procedures on the neoanus between the two protocols suggesting that RPD is unlikely to be a significant factor in deciding the outcomes of the anorectal reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 A recent survey about the pre-and postoperative management of ARMs in selected European centers and a study completed by the German Network for Congenital UroRectal Malformations (CURE-Net) showed that anal dilations are frequently carried on following a different protocol from the one suggested by Peña. 5,6 Moreover, Peña's protocol only suggests general guidelines on how to perform anal dilations and does not advice how often patients need to be followed up, or the attitude toward acute complications that may occur during anal dilations. Therefore, aims of our survey were to investigate the current practice of anal dilations among pediatric surgeons with expertise in colorectal surgery, to understand how many of the participants strictly follow Peña's protocol, to investigate what is the approach toward common complications that can occur during anal dilations, and to evaluate if different modalities to perform dilations may be associated with different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, worldwide anal dilations are not routinely performed by all surgeons, and two recent European works showed that many centers may have created internal protocols for performing anal dilations. [5][6][7] Moreover, it has been suggested that other modalities to perform anal dilations, such as dilating the neoanus once a week rather than daily, can be as effective and safe. 8 Therefore, with our study we aim to assess the current practice of anal dilations after ARM repair in different institutions and to verify if different practices may lead to different outcomes in terms of complications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many of the guidelines can and are interpreted differently by different pediatric surgical departments, for example, dilatation protocols after the final reconstructive surgery. 3 A few large case series have been reported, for example, that of Peña and other colleagues of his center, however, these often report only the experience of a single surgeon. Hence, transfer of published results may not be so easy because some surgeons have a much more limited exposure and the right interpretation depends on definitions used to describe the data.…”
Section: Introductionmentioning
confidence: 99%